MARKET INTEGRATION OF CORN (Zea mays) IN TUBAN DISTRICT - Inong Hasti Yunika; Ratya Anindita; Putri Budi Setyowati (Socio-Economics/Agribusiness Department, 2020)
Market integration is one indicator of marketing efficiency, especially price efficiency, which is a measure that shows the extent to which price changes that occur in the reference market will cause changes that occur in market followers. The difference in prices received by farmers, wholesalers, and retailers in Indonesia in 2011-2015 has increased and decreased by an unequal amount, which means that price changes among marketing agents are not balanced. Agribusiness market participants currently do not use market communication information system services on time so that it will cause information asymmetry and indicate that the market is not integrated. This study analyzes market integration based on the relationship between corn prices at the level of producers, wholesalers, and retailers. The analytical methods used are Engle-Granger cointegration, Error Corection Model (ECM), and Granger Causality Test. The results show that the corn market between producers and wholesalers, between wholesalers and retailers, and between producers and retailers has been integrated in the long and short term. Market information needs to be improved so that market integration is stronger.